New discovery of obligatory diapause in egg stage of Pseudodoniella sp. (Hemiptera: Miridae) in Chi Lang district, Lang Son province - Lam, Pham Van; Dung, Hoang Thi (Academia Journal of Biology, 2012)
This paper presents the result of study on obligatory diapause of plant bug Pseudodoniella sp. (Hemiptera: Miridae) in Chi Lang district, Lang Son province. The appearance of Pseudodoniella sp. and its population fluctuation on custard apple was surveyed in two successive years (2007-2008) in Chi Lang district, Lang Son province. The results of our research showed that the plant bug Pseudodoniella sp. was appeared annually on custard apple from April to September with fluctuated population density. The first appearance of Pseudodoniella sp. in each year coincided with the emergence of new spring flushes. There are no adults and nymphs of the plant bug Pseudodoniella sp. observed on custard apple during the period from October to March of following year. The results obtained from rearing the plant bug Pseudodoniella sp. confined in insect net on custard apple in natural conditions showed that during period from October to March of next year when there is no food and the temperature is not favourable for development, their eggs diapause under outer bark of young custard apple twigs. The finding on obligatory hibernation in egg stage of Pseudodoniella sp. is a new record for insect pests in Vietnam.